1995
DOI: 10.1677/joe.0.1460331
|View full text |Cite
|
Sign up to set email alerts
|

The effects of oestradiol and relaxin on extensibility and collagen organisation of the pregnant rat cervix

Abstract: The effects of exogenously introduced oestradiol-17 beta (E) and relaxin (RLX) on cervical extensibility and collagen organisation were tested in rats ovariectomised in late pregnancy. When the cervices were stretched in vitro by 1 mm increments, it was found that those from rats given E alone generated significantly higher tensions than those from control rats, while cervices from rats given both E and RLX had tensions similar to controls. Examination of cervical sections under the light microscope and ultra-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…Previously, we and others have shown in animal models that relaxin can alter the three-dimensional structure of collagen fibers within remodelling tissue (6,26). In our model, capsules formed around subcutaneously implanted relaxinfilled osmotic pumps were comprised of collagen fibrils that were less densely packed and frequently not in ordered parallel arrays to the same extent as they appeared in capsules formed around vehicle-loaded pumps.…”
Section: Discussionmentioning
confidence: 70%
“…Previously, we and others have shown in animal models that relaxin can alter the three-dimensional structure of collagen fibers within remodelling tissue (6,26). In our model, capsules formed around subcutaneously implanted relaxinfilled osmotic pumps were comprised of collagen fibrils that were less densely packed and frequently not in ordered parallel arrays to the same extent as they appeared in capsules formed around vehicle-loaded pumps.…”
Section: Discussionmentioning
confidence: 70%
“…This finding is of interest because it indicates that the acute effects of relaxin on cervical growth and softening either require different thresholds of NO and/or are mediated by different mechanisms. Numerous studies have demonstrated that relaxin-induced softening of the rat cervix is accompanied by a reduction in the density and organization of collagen fiber bundles in the extracellular matrix (1,6,44,45), and it is generally accepted that this remodeling of collagen fibers contributes to cervical softening. Signal molecules that play key roles in relaxininduced remodeling of the cervix have not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Oestrogen becomes the dominant hormone at parturition in the ewe, when it induces cervical ripening (Ellwood 1980, Winn et al 1994, Cheah et al 1995, Silva et al 1995 and the formation of myometrial gap junctions (Garfield et al 1980, Ciray et al 1996. Although the Figure 4 The expression of oestradiol receptor (E2R) mRNA in the maternal caruncles or villi was localised by in situ hybridisation.…”
Section: Discussionmentioning
confidence: 99%